Sensory Integration in Human Movement: A New Brain-Machine Interface Based on Gamma Band and Attention Level for Controlling a Lower-Limb Exoskeleton - Ortiz, Mario; Ferrero, Laura; Iáñez, Eduardo; Azorín, José M.; Contreras-Vidal, José L. (Frontiers in Bioengineering and Biotechnology, 2020)
Brain-machine interfaces (BMIs) can improve the control of assistance mobility devices making its use more intuitive and natural. In the case of an exoskeleton, they can also help rehabilitation therapies due to the reinforcement of neuro-plasticity through repetitive motor actions and cognitive engagement of the subject. Therefore, the cognitive implication of the user is a key aspect in BMI applications, and it is important to assure that the mental task is correlated with the actual motor action. However, the process of walking is usually an autonomous mental task that requires a minimal conscious effort. Consequently, a brain-machine interface focused on the attention to gait could facilitate sensory integration in individuals with neurological impairment through the analysis of the voluntary gait will and its repetitive use. This way the combined use of BMI+exoskeleton turns assistance to restorative. The paper presents a new brain-machine interface based on the decoding of gamma band activity and attention level during motor imagery mental tasks. The work shows a case of study tested in able-bodied subjects prior to a future clinical study, demonstrating that a BMI based on gamma band and attention level paradigm allows real-time closed-loop control of a Rex exoskeleton.